2012
DOI: 10.1021/es302321n
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Short-Chain Chlorinated Paraffins in China, Japan, and South Korea

Abstract: This study presents the first investigation of concentrations and congener group patterns of atmospheric short-chain chlorinated paraffins (SCCPs) throughout East Asia. Based on an absorption rate calibration experiment, a spatial survey of SCCPs was performed using passive air samplers in China, Japan, and South Korea during two separate periods in 2008. The atmospheric concentrations of SCCPs in China were clearly greater than those in Japan and South Korea, both of which exceed the levels determined for oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 28 publications
10
95
3
Order By: Relevance
“…The levels in bark were somewhat higher in winter (GM 20.50 mg/g lw) than summer (13.9 mg/g lw) although the difference was not statistically significant (ManneWhitney U, p ¼ 0.06), and needle concentrations clearly showed no significant differences between winter (GM 11.7 mg/g lw) and summer (GM 11.9 mg/g lw). This was in contrast to the ambient air levels of SCCPs in Beijing using active air sampler and also around East Asia using passive air samplers, where higher summer levels were found Li et al, 2012).…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…The levels in bark were somewhat higher in winter (GM 20.50 mg/g lw) than summer (13.9 mg/g lw) although the difference was not statistically significant (ManneWhitney U, p ¼ 0.06), and needle concentrations clearly showed no significant differences between winter (GM 11.7 mg/g lw) and summer (GM 11.9 mg/g lw). This was in contrast to the ambient air levels of SCCPs in Beijing using active air sampler and also around East Asia using passive air samplers, where higher summer levels were found Li et al, 2012).…”
Section: Resultscontrasting
confidence: 84%
“…Active air samplers and passive air samplers are frequently used to investigate the atmospheric levels and distribution of SVOCs (Hayward et al, 2010), but these need to be deployed at each site and revisited during collection. These sampling methods have also been previously used for evaluating the levels of SCCPs in the atmosphere (Wang et al, , 2013Li et al, 2012). On the other hand, vegetation can also accumulate considerable amounts of SVOCs from the atmosphere by gas-phase partitioning process and/or deposition of particle bound residues.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, our results were comparable to the air concentrations of SCCPs all over China but higher than those in Japan and South Korea in 2008. 6 The air concentrations of CPs varied widely with the sampling sites (Figure 2a). Spatial distribution showed that a gradient of CP concentrations from more to less industrialized areas was discovered, mainly impacted by the proximity to primary point sources.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…1,4 Meanwhile, SCCPs are under review by the Stockholm Convention as a potential "new" category of POP due to their persistence, bioaccumulation, long-range transport potential, and toxic character. 5,6 As reported, SCCPs show chronic toxicity in aquatic organisms and are carcinogenic in rats and mice. 7 The toxicity of MCCPs is lower compared to SCCPs, but they are widely used and show higher concentration levels than SCCPs.…”
Section: ■ Introductionmentioning
confidence: 92%
“…S2). Specifically, C 10 Cl 6-8 congeners were the prevailing ones in water samples (Lu, 2013;Yuan et al, 2012;Zeng et al, 2011bZeng et al, , 2012aZeng et al, , 2012b, while those with 5-7 chlorine atoms were dominant in air samples (Chaemfa et al, 2014;Fridén et al, 2011;Li et al, 2012;Wang et al, 2012Wang et al, , 2013bWang et al, , 2015. As for sediment and soil samples, the most abundant congeners possessed 5-10 chlorine atoms (Chen et al, 2011;Gao et al, 2012;Hüttig and Oehme, 2006;Iino et al, 2005;Iozza et al, 2008;Marvin et al, 2003;Štejnarová et al, 2005;Tomy et al, 1999;Wang et al, 2013bWang et al, , 2013cZeng et al, 2011aZeng et al, , 2012cZeng et al, , 2013, quite similar to those in food, human milk and wildlife samples (Harada et al, 2011;Thomas et al, 2006;Zeng et al, 2011b).…”
Section: Effect Of Chlorination Degree On Thermodynamic Properties Ofmentioning
confidence: 82%